Novel technique for repairing episiotomy incisions to achieve optimal vaginal and perineal anatomy - Shobhane, Hema J.; Sharma, Diksha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Episiotomy is one of the most commonly practiced obstetric procedures done to enlarge the diameter of the vulval outlet to facilitate the passage for the fetal head and prevent an uncontrolled tear of the perineal tissues in the second stage of labor. The study compared the effectiveness of the new technique with the standard technique in promoting proper tissue healing, reducing discomfort and minimizing the risk of complications. Methods: The prospective comparative study was conducted for duration of 15 years. Women who were primigravida, with singleton pregnancy, at term gestation, with vertex presentation were included in the study and women with multigravida, multiple pregnancy, preterms were excluded from the study. Episiotomies were performed either novel technique or traditional technique by random allocation and results were compared. Results: At 6 weeks and 1 year, 80% and 95% patients had no pain who had episiotomy repaired by novel technique. At one year follow up 1% patients had vaginal discharge who had episiotomy repaired by novel technique while 6% who had episiotomy repaired by traditional technique. 78% patients were psychologically satisfied with episiotomy repaired by novel technique. Conclusions: Novel technique of episiotomy suturing is recommended for less postoperative complications, cosmetic pleasing aesthetic outcome and psychological satisfaction.